Formation of the All India Muslim League and its Response to some Foreign Issues – 1906 – 1911 - Nadeem Shafiq Malik (Journal of Political Studies, 2012)
The All India Muslim League (AIML) was formed on December 30, 1906 mainly to protect and advance the political rights and interests of the Muslims of India but the extra-territorial issues also did not escape its attention. Therefore, references to the international issues continued to emerge in the AIML proceedings in the coming years. The first major international issue which attracted the AIML’s attention was mistreatment of the Indians in the British colonies particularly in the Transvaal state of South Africa. The AIML urged the British cabinet to secure complete and equal rights and privileges of the British citizenship for the Indians with a permission to settle in the British colonies on equal terms with the ‘white races’. The Pan-Islamic sentiments also got reflected in the AIML proceedings. However, international concerns of the AIML, rather whole of the Muslim India, were best exhibited in the case of Turkey.